HUBUNGAN USIA DAN PENGGUNAAN KONTRASEPSI DENGAN GAMBARAN HISTOPATOLOGI KANKER OVARIUM DI RSPAD GATOT SOEBROTO TAHUN 2019-2020 - Dewa Ayu Metha Saraswati (2023)
Introduction: Ovarian cancer is a malignant tumor with a poor prognosis and a high mortality rate, generally the diagnosis is made at an advanced stage. The incidence of ovarian cancer increases with age and reaches a peak at the age of 65 years. There are several factors that can affect the risk of ovarian cancer. Several studies have stated that the use of contraceptive method can reduce the risk of developing these cancers. Purpose: The purpose of this study was to determine the relationship between age and contraceptive use with the histopathological features of ovarian cancer at Gatot Soebroto Army Hospital in 2019-2020. Method: This research is observational analytic research with a cross-sectional study design using medical record data of 104 ovarian cancer patients. The data was analyzed using the chi-square test. Result: The results of bivariate analysis showed a p=0.000 for the relationship of age and the histopathological type of ovarian cancer and p=0.545 for the relationship of contraceptive use and the histopathological type of ovarian cancer. Conclusion: There is a significant relationship between age and the histopathological type of ovarian cancer and there is no significant relationship between contraceptive use and the histopathological type of ovarian cancer.